The language of the Danziger in the works of Günter Grass - Bednarska-Kociołek, Joanna (Acta Universitatis Lodziensis. Folia Germanica, 2016)
In his works Günter Grass tackles subjects connected with the tradition and identity of Gdańsk citizens. In this article I will first consider the most important languages in the culture of the city. Gdańsk citizens used to speak in a mixed language, because representatives of different nationalities, Poles, Germans, Jews and Kashubians lived here. At home they used Polish or Kashubian and at work or in offices standard German. For Grass and his heroes Kashubian , East Low German (Plautdietsch) or Polish were the languages of their hearts. These languages were expressed in contexts most closely associated with the home, most frequently those of food, leisure or vacations. In this article the „we-community“ (Hobsbawm 1998, S. 7) of Gdańsk, which does not exist anymore, is discussed. Thanks to the writer, readers can become acquainted with the city and its colour.